ATMOSPHERIC RADIOCARBON FOR THE PERIOD 1950–2019. Issue 4 (23rd August 2022) - Hua, Quan; Turnbull, Jocelyn C; Santos, Guaciara M; Rakowski, Andrzej Z; Ancapichún, Santiago; De Pol-Holz, Ricardo; Hammer, Samuel; Lehman, Scott J; Levin, Ingeborg; Miller, John B; Palmer, Jonathan G; Turney, Chris S M
ABSTRACT: This paper presents a compilation of atmospheric radiocarbon for the period 1950–2019, derived from atmospheric CO2 sampling and tree rings from clean-air sites. Following the approach taken by Hua et al. (2013 ), our revised and extended compilation consists of zonal, hemispheric and global radiocarbon ( 14 C) data sets, with monthly data sets for 5 zones (Northern Hemisphere zones 1, 2, and 3, and Southern Hemisphere zones 3 and 1–2). Our new compilation includes smooth curves for zonal data sets that are more suitable for dating applications than the previous approach based on simple averaging. Our new radiocarbon dataset is intended to help facilitate the use of atmospheric bomb 14 C in carbon cycle studies and to accommodate increasing demand for accurate dating of recent (post-1950) terrestrial samples.